1999
DOI: 10.1177/096120339900800608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of soft tissue calcifications in patients with SLE and effects of alfacarcidol

Abstract: It is suggested that the alfacarcidol therapy and lupus nephritis could increase the risk of ectopic calcification in SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
(32 reference statements)
0
11
0
1
Order By: Relevance
“…22 In a few cases, SLE was associated with extensive ulcerating skin calcification and multiple subcutaneous calcified deposits. 22,24 An unusually high prevalence of ectopic calcification in SLE patients was reported by Okada et al, 25 who found calcification in periarticular areas in 33% of cases and in other soft tissues in 17%.…”
Section: Learning Objectivesmentioning
confidence: 84%
“…22 In a few cases, SLE was associated with extensive ulcerating skin calcification and multiple subcutaneous calcified deposits. 22,24 An unusually high prevalence of ectopic calcification in SLE patients was reported by Okada et al, 25 who found calcification in periarticular areas in 33% of cases and in other soft tissues in 17%.…”
Section: Learning Objectivesmentioning
confidence: 84%
“…Calcification and systemic deposition of calcium salts have been described in multiple autoimmune diseases, including scleroderma, dermatomyositis, rheumatoid arthritis, Sjögren syndrome, and SLE, with a mean age of onset of 33.3 years. 13,14 The deposition of calcification can be idiopathic, dystrophic, or due to calciphylaxis, and while the pathophysiology is unclear, it is thought to relate to circulating chronic inflammatory mediators. [15][16][17][18][19][20][21][22][23][24][25][26][27] Case reports describe both focal and extensive systemic deposition of calcification in patients with both rheumatoid arthritis and SLE, with calciphylaxis described as a rare complication of both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with JDM, dystrophic calcinosis often occurs in the subcutaneous tissues or in the muscles around the flexor side of the elbows or knees. Okada et al [5] reported that dystrophic calcinosis rarely appears in association with SLE. With regard to RA, there were no other reports of dystrophic calcinosis.…”
Section: Discussionmentioning
confidence: 99%